2022
DOI: 10.1017/s0954579421001644
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver–child proximity as a dimension of early experience

Abstract: Human infancy and early childhood is both a time of heightened brain plasticity and responsivity to the environment as well as a developmental period of dependency on caregivers for survival, nurturance, and stimulation. Across primate species and human evolutionary history, close contact between infants and caregivers is species-expected. As children develop, caregiver–child proximity patterns change as children become more autonomous. In addition to developmental changes, there is variation in caregiver–chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 161 publications
0
13
0
Order By: Relevance
“…Furthermore, even though the effect of visual contact on IMS appeared to be stronger when participants were closer, we found no evidence of a significant interaction. Provided that a relationship between interpersonal spatial proximity and social behavior is to be expected given previous research, 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 we might not have observed it because of two possible reasons. Either the effect of interpersonal spatial proximity was mitigated by other changing variables that we did not measure such as, for instance, attentional focus (see e.g., 76 , 80 , 81 , 82 ), or we might conclude that such relationship does not necessarily manifest in terms of IMS.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, even though the effect of visual contact on IMS appeared to be stronger when participants were closer, we found no evidence of a significant interaction. Provided that a relationship between interpersonal spatial proximity and social behavior is to be expected given previous research, 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 we might not have observed it because of two possible reasons. Either the effect of interpersonal spatial proximity was mitigated by other changing variables that we did not measure such as, for instance, attentional focus (see e.g., 76 , 80 , 81 , 82 ), or we might conclude that such relationship does not necessarily manifest in terms of IMS.…”
Section: Discussionmentioning
confidence: 90%
“…Reducing this large discrepancy may offer numerous psychological benefits. In WEIRD studies, increased contact has been shown to increase maternal sensitivity; promote secure attachment; enhance brain development and learning abilities; and reduce depressive symptoms in mothers, in turn providing indirect benefits for their babies (W. Barnett et al, 2022;Little et al, 2018;Norholt, 2020). The extensiveness of contact found here implies that the psychological returns on increased contact may follow a dose-response relationship that extends far beyond the range of WEIRD contact levels, and even beyond intervention studies of the benefits of contact.…”
Section: Levels Of Closenessmentioning
confidence: 59%
“…Although the authors also coded maternal touches, they found that the touches occurred relatively rarely and thus dropped them from the analyses. Thus, it may be that proximity, an important aspect of parent–infant interaction (Barnett et al., 2021), rather than physical touch, exerts influence over infants’ oxytocin system. Inspired by these results, we also looked into caregiver–infant proximity during free play (analyses reported in the Supporting Information), but found no evidence of associations between proximity and oxytocin or social orienting.…”
Section: Discussionmentioning
confidence: 99%